Fiscal Risk Management for Development : The Case of Colombia - Salazar, Natalia (World Bank, Washington, DC, 2013)
Colombia’s strong fiscal-institutional framework has been one of the main elements that explains the resilience of the Colombian economy to global economic turbulence. The consolidation of the fiscal framework has been a gradual process over the last 15 years and was strengthened with the enactment of the Responsibility and Transparency Law in 2003. This paper emphasizes the establishment of Medium Term Fiscal Plan (MTFF) which introduced a useful tool for macro-fiscal programming and set high standards for the transparency and management of fiscal policies and risks.